Association of Gestational Vitamin E Status With Pre-eclampsia: A Retrospective, Multicenter Cohort Study - Shi, Huifeng; Jiang, Yuanhui; Yuan, Pengbo; Chen, Lian; Gong, Xiaoli; Yang, Yike; Wang, Yuanyuan; Jiang, Hai; Li, You; Sun, Mengxing; Zhao, Yangyu; Wei, Yuan (Frontiers in Nutrition, 2022)
Introduction: Pre-eclampsia is the second leading cause of maternal mortality worldwide. The controversy for the association of vitamin E with pre-eclampsia has raged unabated for two decades. We aimed to determine the association of vitamin E level in the first trimester and the gestational change with pre-eclampsia. Materials and Methods: A retrospective cohort study was conducted among singleton pregnant women aged 15–49 years at 137 hospitals in China. Serum vitamin E concentrations in the first trimester and at pre-eclampsia assessment time were uniformly quantified in a laboratory by high performance liquid chromatography. Logistic regression models with restricted cubic splines were performed to reveal a nonlinear L-shaped association of vitamin E concentrations in the first trimester and the gestational change with pre-eclampsia. Results: We included 73 317 participants (47.8% aged 25–29 years) and 2.28% were diagnosed with pre-eclampsia. Higher risk was observed in those with lower concentration in the first trimester and greater gestational decrease, with a range from 1.28% to 63.69%. A nonlinear L-shaped association was observed between vitamin E concentrations in the first trimester and pre-eclampsia, suggesting a threshold at 7.3 mg/L and a ceiling effect: the risk saw a steep rise when the concentrations in the first trimester were < 7.3 mg/L but was relatively flat beyond the inflexion point. Sharply increased pre-eclampsia risk was also found in those with gestational vitamin E decrease after accounting for the baseline status in the first trimester. However, gestational vitamin E increase was associated with decreased pre-eclampsia risk when the baseline concentrations were < 7.3 mg/L but did not confer additional benefits when it was above the threshold. Conclusions: We demonstrated alarmingly high pre-eclampsia risk in women with vitamin E concentrations of <7.3 mg/L in the first trimester and gestational vitamin E decrease. These findings underscore the need to supplement vitamin E among pregnant women with low baseline status.